The Texas Immuno-Oncology Biorepository, a statewide biospecimen collection and clinical informatics system to enable longitudinal tumor and immune profiling. Issue 1 (2nd January 2023) - Kelly, Ronan J.; Whitsett, Timothy G.; Snipes, G. Jackson; Dobin, Sheila M.; Finholt, Jennifer; Settele, Natalie; Priest, Elisa L.; Youens, Kenneth; Wallace, Lucy B.; Schwartz, Gary; Wong, Lucas; Henderson, Sherronda M.; et al.
Abstract: A detailed understanding of the molecular and immunological changes that occur longitudinally across tumors exposed to immune checkpoint inhibitors is a significant knowledge gap in oncology. To address this unmet need, we created a statewide biospecimen collection and clinical informatics system to enable longitudinal tumor and immune profiling and to enhance translational research. The Texas Immuno-Oncology Biorepository (TIOB) consents patients to collect, process, store, and analyze serial biospecimens of tissue, blood, urine, and stool from a diverse population of over 100, 000 cancer patients treated each year across the Baylor Scott & White Health system. Here we sought to demonstrate that these samples were fit for purpose with regard to downstream multi-omic assays. Plasma, urine, peripheral blood mononuclear cells, and stool samples from 11 enrolled patients were collected from various cancer types. RNA isolated from extracellular vesicles derived from plasma and urine was sufficient for transcriptomics. Peripheral blood mononuclear cells demonstrated excellent yield and viability. Ten of 11 stool samples produced RNA quality to enable microbiome characterization. Sample acquisition and processing methods are known to impact sample quality and performance. We demonstrate that consistent acquisition methodology, sample preparation, and sample storage employed by the TIOB can produce high-quality specimens, suited for employment in a wide array of multi-omic platforms, enabling comprehensive immune and molecular profiling.